Evaluation of soybean (Glycine max) germplasm for some important morphological traits using multivariate analysis - PAWAR, KSHITIZ KUMAR; RANGARE, N R; SINGH, A K (The Indian Journal of Agricultural Sciences, 2014)
Based on the results obtained in present study, it is advocated that the genotypes namely MACS 1201, SL 788 and MASU 449 were identified as the best genotypes for grain yield. The cluster VII (CSB 08-09) and VI (SL 778, Dsb 20, MACS 1311, RKS 61, BAUS 40) was most diverse to each other. Hence, crossing between these cluster would help to accumulate favorable and desirable alleles for further improvement in grain yield and its component in soybean.